Peran Guru Dan Strategi Guru Dalam Meningkatkan Minat Belajar Pada Pembelajaran Matematika Siswa Kelas IV SDN Burum Kecamatan Bintang Ara Kabupaten Tabalong - Irni Cahyani; Arina Wulandari; Mardatillah Mardatillah (Journal of Humanities, Social Sciences, and Education, 2025)
Interest is a feeling of liking or attraction to something or an activity without anyone asking or telling. This interest in learning can be influenced by many factors, including the student himself, family, and school. A student needs to have a good interest in learning (interest in learning) so that through the stage of interest in learning students can improve learning outcomes. Mathematics learning is a teaching and learning process built by teachers to develop students' creative thinking, and can improve the ability to construct new knowledge as an effort to improve good mastery of mathematics material. Mathematics is one of the most important subjects and is studied from elementary school, junior high school, high school to college. This type of research is qualitative research using a descriptive approach. The subjects of the study were homeroom teachers for grade IV. Data collection techniques through observation, interviews, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study show that the role of teachers and teacher strategies in increasing interest in learning are as follows: (1) The role of teachers is very influential in increasing students' interest in learning. The role of teachers includes being class managers, class supervisors, and student motivators. These three things are interrelated in managing the class. Teachers can pay attention to students, facilitate deeper discussions, and provide learning strategies that are appropriate to students' needs. (2) Teacher strategies are very influential in increasing students' interest in learning. At SDN Burum, grade IV teachers use learning strategies including using cooperative learning, using learning media, and class discussion learning strategies.